2020
DOI: 10.1186/s12889-020-08875-3
|View full text |Cite
|
Sign up to set email alerts
|

African-led health research and capacity building- is it working?

Abstract: Background: Africa bears a disproportionately high burden of globally significant disease but has lagged in knowledge production to address its health challenges. In this contribution, we discuss the challenges and approaches to health research capacity strengthening in sub-Saharan Africa and propose that the recent shift to an African-led approach is the most optimal. Methods and findings: We introduce several capacity building approaches and recent achievements, explore why African-led research on the contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 31 publications
1
96
0
Order By: Relevance
“…A study exploring research infrastructure in Africa reported signi cant resource constraints in terms of supportive policies, legislation, infrastructure, human capacity, and funding (66) that could be areas for NPHIs to support. Recent ndings suggest that local capacity building efforts supporting research may have important dividends (67). Articles focused on how NPHI-led research informed policy decisions has been corroborated by studies demonstrating the return of research investments in the form of increased MoH budgets (68) and policy reform (69).…”
Section: Discussionmentioning
confidence: 99%
“…A study exploring research infrastructure in Africa reported signi cant resource constraints in terms of supportive policies, legislation, infrastructure, human capacity, and funding (66) that could be areas for NPHIs to support. Recent ndings suggest that local capacity building efforts supporting research may have important dividends (67). Articles focused on how NPHI-led research informed policy decisions has been corroborated by studies demonstrating the return of research investments in the form of increased MoH budgets (68) and policy reform (69).…”
Section: Discussionmentioning
confidence: 99%
“…A study exploring research infrastructure in Africa reported significant resource constraints in terms of supportive policies, legislation, infrastructure, human capacity, and funding (Kirigia & Wambebe, 2006) that could be areas for NPHIs to support. Recent findings suggest that local capacity building efforts supporting research may have important dividends (Kasprowicz et al, 2020). Articles focused on how NPHI-led research informed policy decisions has been corroborated by studies demonstrating the return of research investments in the form of increased MoH budgets (González-Block, 2009) and policy reform (Knaul et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We have argued that the macro-level forces of neo-colonial relationships in funding structures exacerbates the racism in grant allocation as perceived by African scientists. Others have similarly posited that the challenges around funding structures are external to Africa, and are engrained in legacies of colonialism that continue to favour Northern-based researchers as parachute researchers (41). This problem is exacerbated by requiring grant applicants to hold a faculty position, without acknowledging the biases on the basis of ageism, favouritism and nepotism in provision of tenure that are common in higher education institutions in Africa (9,28,42).…”
Section: Discussionmentioning
confidence: 99%